The Psychometric Properties of the Norwegian version of Vineland Adaptive Behavior Scales-Second Edition (Vineland-II) - Heyerdahl, Sonja; Eikeseth, Svein (PsykTestBarn, 2014)
Description: Vineland Adaptive Behavior Scales (Vineland ABS) have been extensively used for the assessment of adaptive behaviors (personal and social skills needed for everyday living). The scales were first published in 1984 in the USA. Vineland-II is an extensive revision, published in 2005; a Scandinavian version with Scandinavian norms in 2011. NCS Pearson Inc. has the copyright. The Scandinavian Vineland-II has three scale versions: a survey interview form, a survey parent/caregiver rating form and a teacher rating form. The content and scales are organized within a three-domain structure (indexes) for the age group 2-21 years: Communication, Daily Living Skills, and Socialization, with an additional Motor Skills Domain (< 7 years). Results sum up to an Adaptive Behavior Composite. Literature search: The literature search for Norwegian, Danish and Swedish articles with information about the psychometric properties of Vineland-II identified 33 references. Only one paper had used Vineland-II, and this paper did not report relevant psychometric results. Scandinavian (Swedish-Danish-Norwegian) norms for the parent/caregiver rating form were reported in the Norwegian Vineland-II manual. Psychometrics: Our evaluation of the psychometric properties of the scales is based on data from the manual (a Scandinavian representative cross-sectional study; N=1673). Extensive norm data are reported. Good agreement between Vineland-II results and established diagnostic evaluations support content validity. Confirmatory factor analyses support the structure of the scales. Results from a small study of children with autism showed deviances as expected. Internal consistency and split-half reliability were very satisfactory for both the Adaptive Behavior Composite and the Index scores (> 0,90), with the exception of Motor Skills for some age groups). Conclusion: The Scandinavian version of Vineland-II has recently been published, and relevant Norwegian or Scandinavian studies have not yet been published, except for those reported in the manual. The Scandinavian norms seem to be representative. The manual provides a system for extensive reports of the results for a child, based on the Scandinavian norms. Psychometric results indicate good psychometric properties for the parent/caregiver rating form. The survey interview form, which is completed by an interviewer corresponds with the parent/caregiver rating form, but it is not documented that the norms or the psychometric properties of this version are the same as those for the parent/caregiver rating form.